Effect of Universal Adhesives on Long-term Bond Strength to Zirconia - Monteiro, Renata Vasconcelos; dos Santos, Daniela Micheline [UNESP]; Chrispim, Bruna; Bernardon, Jussara Karina; Porto, Thiago Soares; De Souza, Grace Mendonça (My University, 2022)
Purpose: To evaluate the effect of universal adhesives on the long-term bond strength to yttria-stabilized tetragonal zirconia polycrystal (Y-TZP). Materials and Methods: Polyethylene tubes filled with composite cement containing 10-methacryloyloxydecyl dihydrogen phosphate (10-MDP) were adhesively luted to 60 fully sintered Y-TZP slabs (7 x 7 x 2 mm) with or without (control) previous application of a 10-MDP-based adhesive (All Bond Universal, Bisco) – ABU; Clearfil Universal Bond Quick, Kuraray Noritake – CUB; Scotchbond Universal Adhesive, 3M Oral Care – SUA) on the zirconia surface. The bonded specimens were stored in water for 24 h, 6 months, or 1 year and subjected to microshear bond strength testing. The data were analyzed by one-way ANOVA and Tukey’s test (p < 0.05). The contact angle was measured after adhesive application to evaluate surface wettability. The adhesive-treated specimens were analyzed with x-ray photoelectron spectroscopy (XPS) and time-of-flight secondary ion mass spectrometry (ToF-SIMS) for chemical characterization. Results: The application of a 10-MDP-based adhesive significantly improved bond strength of composite cement to zirconia when compared to the control group (no adhesive application) (p < 0.05). One-year water storage significantly decreased bond strength for ABU and CUB-bonded specimens, but not for SUA-bonded specimens. The analysis by XPS and ToF-SIMS showed peaks of carbon, phosphorus, and silicon in all adhesive-treated specimens. Conclusions: One-year water storage affected the bond strength of composite cement to zirconia when All Bond Universal or Clearfil Universal Bond Quick were used.
Keywords: Composite cement; Dental ceramic; Microshear bond strength; Universal adhesive